Genotoxicity and Safety Pharmacology Studies of Indole Alkaloids Extract from Leaves of Alstonia scholaris (L.) R. Br. - Yun-Li Zhao (Natural Products and Bioprospecting, 2020)
Abstract Indole alkaloids extract (IAAS) was prepared from leaves of Alstonia scholaris (L.) R. Br., an evergreen tropical plant widely distributed throughout the world. This plant has been used historically by the Dai ethnic people of China to treat respiratory diseases. This study evaluated the genotoxicity and safety pharmacology of IAAS to support clinical use. The bacterial reverse mutation (Ames) test, in vitro mammalian chromosomal aberration test, and in vivo mammalian erythrocyte micronucleus (MN) test were performed to evaluate genotoxicity. Mice were administered IAAS (240, 480, or 960 mg/kg bw) once orally to observe adverse central nervous system effects. Furthermore, beagle dogs were administered IAAS (10, 30, 60 mg/kg bw) once via the duodenum to evaluate its effects on the cardiovascular and respiratory systems. IAAS with or without S9-induced metabolic activation showed no genotoxicity in the Ames test up to 500 μg/plate, in the mammalian chromosomal aberration test up to 710 μg/mL, or in the MN test up to 800 mg/kg bw. No abnormal neurobehavioral effects were observed in mice following treatment with up to 960 mg/kg bw of IAAS. Moreover, blood pressure, heart rate, electrocardiogram parameters, and depth and rate of breathing in anesthetized beagle dogs did not differ among the IAAS doses or from the vehicle group. These data indicated that IAAS did not induce mutagenicity, clastogenicity, or genotoxicity, and no pharmaco-toxicological effects were observed in the respiratory, cardiovascular, or central nervous systems. Our results increased understanding of safety considerations associated with IAAS, and may indicate that IAAS is a possible drug candidate. Graphic Abstract